A personnel profile of professional nurses in the J.D. Allen operating theatre complex of Baragwanath Hospital - E.F. Smith; H.H.M. Uys (AOSIS, 1991)
In this exploratory descriptive study an attempt was made to develop a profile of professional nurses in the J.D. Allen operating theatre complex of Baragwanath hospital. Aspects of significance have been extracted front the analysed data and highlighted as trends, not only of demographic nature but also in nursing education and practice, with specific reference to operating theatre nursing. Problem areas have been indicated and recommendations suggested. This profile could be used as a staff development tool. It also would be possible to plan more rational staff structure considering future advances.